2012
DOI: 10.1007/s11606-012-2057-x
|View full text |Cite
|
Sign up to set email alerts
|

Two-year Trends in Cancer Screening Among Low Socioeconomic Status Women in an HMO-based High-deductible Health Plan

Abstract: BACKGROUND: Cancer screening is often fully covered under high-deductible health plans (HDHP), but low socioeconomic status (SES) women still might forego testing. OBJECTIVE: To determine the impact of switching to a HDHP on breast and cervical cancer screening among women of low SES. DESIGN: Pre-post with comparison group. PARTICIPANTS: Four thousand one hundred and eighty-eight health plan members enrolled for one year before and up to two years after an employer-mandated switch from a traditional HMO to an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…8,21,23,24 The propensity score models used logistic regression to predict the likelihood of switching to an HDHP versus remaining in a traditional HMO based on age, sex, Adjusted Clinical Groups score, neighborhood education and poverty levels (from census-based geocoded data, below), family versus individual plan, index date, employer size, and baseline outpatient, ED, and hospital copayments. We also conducted sensitivity analyses using 2:1 and 1:1 matches.…”
Section: Methodsmentioning
confidence: 99%
“…8,21,23,24 The propensity score models used logistic regression to predict the likelihood of switching to an HDHP versus remaining in a traditional HMO based on age, sex, Adjusted Clinical Groups score, neighborhood education and poverty levels (from census-based geocoded data, below), family versus individual plan, index date, employer size, and baseline outpatient, ED, and hospital copayments. We also conducted sensitivity analyses using 2:1 and 1:1 matches.…”
Section: Methodsmentioning
confidence: 99%
“…20 The health insurance industry has taken steps to encourage patients to demand pricing transparency through innovative health insurance benefits designs. Such innovations include high-deductible health plans and reference pricing in which insurance provides a fixeddollar contribution toward a given procedure with the patient responsible for any additional cost 21,22 ; both designs are meant to provide incentive for patients to think about cost in addition to other factors. Our results suggest that such efforts at pricing transparency have not been well integrated into the operations at many hospitals.…”
Section: Commentmentioning
confidence: 99%
“…A number of prior papers has found no difference among CDHP enrollees in cancer screening rates (Rowe et al 2008; Wharam et al 2008; Wharam et al 2012). Fronstin et al (2013) found a decrease in the first year after enrollment, but no effect after year two.…”
Section: Related Literaturementioning
confidence: 94%
“…One is that most of these studies use data from a single treatment employer (Fronstin et al 2013; Brot-Goldberg et al 2017) or a single insurance carrier (Wharam et al 2008; Wharam et al 2011; Wharam et al 2012; Fronstin et al 2013; Brot-Goldeberg et al 2017; Rowe et al 2008; Charlton et al 2011). Because of the small number of treated units, idiosyncratic changes may drive the results.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation